Flowering and Fruiting Phenology of Plants of a Dry Deciduous Forest in the Aravalli Hills of Rajasthan, India - Chhangani, Anil Kumar (Indian Forester, 2004)
Plant phases and their phenological events in time and space were recorded in respect of flower buds, nature flowers, unripe fruit and ripe fruits. Out of 214 plants species, collected in the Kumbhalgarh Wildlife Sanctuary (KWS) 45 species were examined for their different phytophases. The phenological scores of each species and their phytophases were examined between January 1997 to December 1997. The phenology study in KWS suggests that this dry-deciduous forest produced enough flowers and fruits available throughout the year, even in the difficult conditions like in summer, to support wild and domestic animals. The majority of species flowered in the hot season. The peak month for flowering was April, whereas fruting takes place round the year with some peak in May but, concentration of ripe and unripe fruits were common during monsoon.